Generation of three isogenic human induced pluripotent stem cell lines from normal neonate skin fibroblasts - Sandelin, Sanne (Netherlands, 2025)
Characterized human induced pluripotent stem cell lines are important for basic research. Here, we report the establishment of three isogenic human induced pluripotent stem cell (hiPSC) lines generated from normal neonate male skin fibroblasts. Pluripotency was induced using the integration free Sendai virus reprogramming method. The pluripotency, identity, quality, and safety of the lines were confirmed to establish characterized human induced pluripotent stem cell lines to be used as normal control cell lines in future studies.